Competitive Intelligence to Improve Business Performance of the Banking Industry in Indonesia - Pedro Prasetyo, Carolus Boromeus (The Islamic Education and Multiculturalism Foundation, 2024)
The banking industry faces challenges from economic and political turmoil. The emergence of various new competitors and technological developments pose threats and vulnerabilities to the banking world. The various challenges, threats and opportunities facing the banking industry today constitute a VUCA (Volatility, Uncertainty, Complexity and Ambiguity) situation. In facing these conditions, it is important for the banking industry to be able to have adaptive capabilities to all existing changes, vulnerabilities and threats. The strategy that can be implemented is competitive intelligence (CI). This research uses a qualitative approach with a literature study method in conducting analysis. This research analyzes changes, vulnerabilities and threats faced by the banking industry. This research then provides analysis and recommendations for implementing competitive intelligence (CI) strategies so that companies have adaptive capabilities and strategies in competing. The analysis was carried out based on 4 aspects of CI, including: commercial and marketing intelligence, competitor intelligence, technological intelligence, and strategic and social intelligence.